Adequate immune response after SARS‐CoV‐2 infection and single dose vaccination despite rapid heart transplantation. (4th October 2021) - Erbel‐Khurtsidze, Sophiko; Immohr, Moritz Benjamin; Akhyari, Payam; Tudorache, Igor; Aubin, Hug; Bruno, Raphael Romano; Westenfeld, Ralf; Feldt, Torsten; Lübke, Nadine; Lichtenberg, Artur; Boeken, Udo
Abstract: Adequate immune response to vaccination remains a challenge in patients after solid organ transplantation. We report a case of a 61‐year‐old male patient who received a left ventricular assist device as a bridge to transplant therapy. Three months before transplantation, he suffered mild SARS‐CoV‐2 infection and was successfully discharged thereafter. Eight days before his successful heart transplantation, he received mRNA BNT 162b2 vaccination. Immediately after transplantation, we detected sufficient rise of nucleocapsid and spike antibodies despite immune suppression therapy. We suspect potential booster effects of the previous SARS‐CoV‐2 infection giving rise to adequate immune response following single vaccination.